QPLAN: Decision support for evaluating planning quality in software development projects - Amaral Féris, Marco Antônio (Elsevier, 2017)
Decisions about whether or not to approve a project plan for execution are critical. A decision to continue with a bad plan may lead to a failed project, whereas requesting unnecessary additional planning for an already high-quality plan may be counterproductive. However, these decisions can be influenced by psychological biases, such as the endowment effect, optimism bias and ambiguity effect, which are enhanced when uncertainty is substantial and information incomplete. As a result, a non-biased model for evaluating the quality of project planning is important to improve planning approval decisions and resource allocation. This paper introduces a novel artifact (QPLAN) that evaluates and improves planning quality, and a case study to demonstrate its effectiveness within a business environment.
Keywords: Decision support tool; Dual process theory; Planning quality; Software projects; Planning-performance theory